2015
DOI: 10.1093/gji/ggv465
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stress changes associated with the 2008 May 29MW 6 earthquake doublet in the western South Iceland Seismic Zone

Abstract: two magnitude M W ∼ 6 earthquakes occurred on two adjacent N-S faults in the western South Iceland Seismic Zone. The first main shock was followed approximately 3 s later by the rupture on a parallel fault, about 5 km to the west. An intense aftershock sequence was mostly confined to the western fault and an E-W aligned zone, extending west of the main shock region into the Reykjanes oblique rift. In this study, a total of 325 well-constrained focal mechanisms were obtained using data from the permanent Icelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…It has been argued that part of the latest stress buildup since the 1896 and 1912 events in the eastern part of SISZ manifested as the 1987 Mw 5.9 (centroid moment magnitude) earthquake that occurred at the junction of SISZ and the western flank of EVZ, ~10 km east of the 1912 earthquake (Bjarnason & Einarsson, 1991). In more recent times, two large sequences of earthquakes in the Years 2000 (17 June Mw 6.5 and 21 June Mw 6.4) (Árnadóttir et al, 2001; Stefánsson et al, 2000) and 2008 (29 May; ~Mw 6.3 doublet in a span of 3 s) (Brandsdóttir et al, 2010; Hensch et al, 2016; Hreinsdóttir et al, 2009) have occurred on SISZ (Figure 1d), all on ~N‐S faults (Clifton & Einarsson, 2005; Hjaltadóttir, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that part of the latest stress buildup since the 1896 and 1912 events in the eastern part of SISZ manifested as the 1987 Mw 5.9 (centroid moment magnitude) earthquake that occurred at the junction of SISZ and the western flank of EVZ, ~10 km east of the 1912 earthquake (Bjarnason & Einarsson, 1991). In more recent times, two large sequences of earthquakes in the Years 2000 (17 June Mw 6.5 and 21 June Mw 6.4) (Árnadóttir et al, 2001; Stefánsson et al, 2000) and 2008 (29 May; ~Mw 6.3 doublet in a span of 3 s) (Brandsdóttir et al, 2010; Hensch et al, 2016; Hreinsdóttir et al, 2009) have occurred on SISZ (Figure 1d), all on ~N‐S faults (Clifton & Einarsson, 2005; Hjaltadóttir, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, we can obtain the principal stress direction and the stress ratio R by analyzing focal mechanisms. The spatiotemporal variation of the focal mechanisms can be used to study the state of stress release (Chiba et al, 2012; Hasegawa et al, 2011), the magnitude of the deviatoric stress (Hardebeck & Hauksson, 2001; Hasegawa et al, 2011; Hensch et al, 2016; Huang et al, 2011; Yoshida et al, 2016), the coseismic stress rotation (Hardebeck, 2012; Hauksson, 1994; Huang et al, 2011; Michael, 1987; Otsubo et al, 2013; Vavryčuk, 2015; Zhao et al, 1997), and the postseismic stress recovery (Hardebeck, 2012; Hauksson, 1994; Ickrath et al, 2014; Zhao et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Hensch et al. (2016) conducted stress inversions using aftershocks of the 2008 ∼M6 Ölfus earthquakes, east of the Hjalli‐Ölfus region, and found that SHmax orientations in Hjalli‐Ölfus showed a counterclockwise rotation (36° ± 8° to 35° ± 8°) over the first month, followed by clockwise rotation (35° ± 8° to 40° ± 6°). A more recent study conducted using GPS data from 2001 to 2015 in SISZ to understand the pre‐seismic strain anomalies before the 2008 ∼M6 earthquakes in Ölfus also points to a varying stress field in the region (Árnadóttir et al., 2018).…”
Section: Discussionmentioning
confidence: 99%